Distribution of Bombus haemorrhoidalis Smith and its Interrelationship with Host Plants in Chitwan Annapurna Landscape of Central Nepal - Ghimire, Kishor Chandra; Bhusal, Daya Ram (BMC Journal of Scientific Research, 2021)
Occurrence and variety of flowering host plant of native Bombus pollinators are viewed as basicalternatives than the imported species. The use of native bumblebee species for pollination wasconsidered more significant than imported bumblebees to reduce environmental impact and pestproblems. B. haemorrhoidalis is the most dominant species of Chitwan Annapurna Landscape inagricultural and wild flora during April to September 2019. We followed assessable walking trailsand used insect net for sample collection. The effect of different environmental variables on the floralhost plant resources of this native bumblebee was examined. With eight locations ranging from 1407to 2506 meters above sea level, twenty-seven species of seventeen plant families were identified aspollen and nectar foraging host plants. B haemorrhidalis distribution frequency is correlated withrelative humidity (0.07438968) and altitude (0.495657857). The most visited plant family wasBalsaminaceae and plant was Imatian scrabida. This study gives the knowledge of abundance of hostplants, ecological and biological relationship of the B. haemorrhoidalis in Nepal